Left ventricular deformation mechanics over time in patients with thalassemia major with and without iron overload - Bonios, Michael J. (BMC Cardiovasc Disord, 2021)
BACKGROUND: Myocardial iron overload in patients with thalassemia major (TM) is one of the most important complications. The purpose of the study was to identify advanced echocardiography parameters for early identification of myocardial dysfunction during follow-up of patients with TM. METHODS: Forty TM patients who were 41 ± 5 years old were included in the study and divided into two groups according to cardiac magnetic resonance T2* results (Group 1: Τ2* > 25 ms, Group 2: Τ2* ≤ 25 ms). Liver T2* parameters were also measured. Conventional and deformational echocardiographic parameters were measured at baseline and approximately 2 years later. RESULTS: Thirty-two patients had Τ2* = 34 ± 4 ms (Group 1), and 8 had Τ2* = 17 ± 9 ms (Group 2). Blood consumption was 185 ± 60 and 199 ± 37 ml/kg/yr (p = 0.64), and liver T2* was 4 ± 5 and 17 ± 21 ms (p = 0.01) in Groups 1 and 2, respectively. At baseline, Group 1 had better left ventricular global longitudinal strain (GLS) (− 22 ± 3 vs. − 18 ± 5, p = 0.01) and similar left ventricular ejection fraction (LVEF) (62 ± 5% vs. 58 ± 10%, p = 0.086) than Group 2. At the 28 ± 11-month follow-up, LVEF, GLS, and T2* values in Group 1 (63 ± 3%, − 21 ± 3%, 34 ± 4 ms) and Group 2 (56 ± 11%, − 17 ± 4%, 17 ± 9 ms) did not change significantly compared to their corresponding baseline values. In 8 patients from Group 1, a worsening (> 15%) in LS (p = 0.001) was detected during follow-up, with a marginal reduction in LVEF. CONCLUSIONS: GLS seems to be an efficient echocardiographic parameter for detecting hemochromatosis-related cardiac dysfunction earlier than LVEF. It also seems to be affected by other factors (free radical oxygen, immunogenetic mechanisms or viral infections) in a minority of patients, underscoring the multifactorial etiology of cardiomyopathy.